Reactive modifications of DNA nucleobases for labelling, bioconjugations, and cross-linking - Ivancová, Ivana; Leone, Denise-Liu'; Hocek, Michal (Current opinion in chemical biology, 2019)
Modification of DNA with reactive groups and their post-synthetic transformations are useful for labelling, imaging, bioconjugations and cross-linking with other (bio)molecules. This review summarizes the recent progress in this field and covers transformations of oxo groups, cycloadditions, conjugate additions, alkylations, cross-couplings and other reactions. Examples of applications are given and the practicability and scope of the reactions are discussed.
Keywords: Alkylation; Cycloaddition Reaction; DNA; reagencia zkříženě vázaná; cykloadiční reakce; Cross-Linking Reagents; alkylace